Implementation of Positive Discipline as an Effort to Overcome Bullying at Aisyiyah Surya Ceria Elementary School, Karanganyar - Setyariza, Nur Ayu; Nashir, Muhammad Jafar (Universitas Islam Negeri Sumatera Utara, 2025)
Primary school education is the process of guiding children aged 6-12 years to develop basic intellectual, social and personal abilities that are developmentally appropriate. In this phase, strengthening character education, especially positive discipline, is very important because of the rise of deviant behavior such as bullying. This study aims to apply positive discipline as part of strengthening student character education, and identify and analyze the efforts made by the Principal and teachers at SD ASC Karanganyar in overcoming bullying behavior. This research uses qualitative research. Data collection was carried out through observation, interviews and documentation. Data analysis techniques used qualitative data analysis, namely data reduction, data presentation, and drawing conclusions. The results showed that the Principal and Teachers at SD ASC Karanganyar have implemented the application of positive discipline and combined with students and parents. The application of positive discipline in minimizing bullying actions, namely: 1). Mutual respect between teachers who are role models for children, 2). Establish effective communication with students, 3). Teaching positive discipline instead of punishing, 4). Focus on solutions not punishment, provide encouragement not praise. Cooperation carried out to overcome bullying includes: 1). Association meetings, 2). Motivation class, 3). Collaboration with Sawahita Psychology, 4). Collaboration with Karanganyar Police on bullying prevention socialization.